Navigating the cartographies of trust: how patients and carers establish the credibility of online treatment claims. (10th October 2019) - Petersen, Alan; Tanner, Claire; Munsie, Megan
Abstract: Digital media offer citizens novel ways of 'enacting' health and illness, and treatment and care. However, while digital media may so 'empower' citizens, those searching for credible information will be confronted with various, often‐conflicting claims that may have 'disempowering' effects. This article uses Gieryn's concept of the 'cultural cartography' to explore the criteria that patients and carers employ in establishing the credibility of information on alleged treatments. Drawing on data from interviews with Australian patients and carers who have travelled or considered travelling abroad for unproven commercial stem cell treatments, the article examines how individuals assess rival sources of epistemic authority – science‐based and non‐science‐based – as they search for credible information. As we argue, in a context where conventional treatment options are perceived to be limited or non‐existent – which is likely to be the case with those suffering severe, life‐limiting conditions – and the credibility of sources uncertain, matters of opinion and belief are prone to being interpreted as matters of fact, with potentially far‐reaching implications for citizens' health. Revealing the mechanisms by which individuals ascribe credibility to health information, we conclude, has become crucial as digital media assume a growing role in health and healthcare and governments encourage citizens to become 'digitally literate'.